2015
DOI: 10.1186/s12944-015-0149-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phytosterols and inulin-enriched soymilk on LDL-cholesterol in Thai subjects: a double-blinded randomized controlled trial

Abstract: BackgroundHypercholesterolemia, particularly high LDL-c and non-HDL-c levels, is a traditional risk for cardiovascular disease. Ingestion of diets containing phytosterols and inulin can reduce plasma LDL-c and triglyceride levels, respectively. Phytosterols and inulin-enriched soymilk may be an alternative for a supplemental diet to improve both LDL-c and non-HDL-c to reduce the risk of cardiovascular disease.MethodsTwo hundred and forty subjects who were 18 years old or older and had a baseline LDL-c of 130 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Previously, inulin supplementation (7-18 g/day, 4-6 weeks length) seemed to decrease blood cholesterol effectively in hypercholesterolemic subjects [3]- [5], [7]. Similar results were also seen in a meta-analysis conducted by Wu et al and a study in Thai population [8], [9]. Though the effects of inulin-enriched products on the lipid profile have been confirmed in many ethnicities, little of them is known in Indonesian population.…”
Section: Introductionsupporting
confidence: 76%
“…Previously, inulin supplementation (7-18 g/day, 4-6 weeks length) seemed to decrease blood cholesterol effectively in hypercholesterolemic subjects [3]- [5], [7]. Similar results were also seen in a meta-analysis conducted by Wu et al and a study in Thai population [8], [9]. Though the effects of inulin-enriched products on the lipid profile have been confirmed in many ethnicities, little of them is known in Indonesian population.…”
Section: Introductionsupporting
confidence: 76%
“…Phytosterols are a group of natural bioactive products mainly found in plants and have a similar structure to cholesterol, with no toxicity to humans and animals . Studies have reported that phytosterols can significantly reduce total cholesterol (TC) and low‐density lipoprotein cholesterol (LDL‐C) in the blood, and increase the index of high‐density lipoprotein cholesterol (HDL‐C)/LDL‐C and HDL‐C/TC …”
Section: Introductionmentioning
confidence: 99%
“…[9] Studies have reported that phytosterols can significantly reduce total cholesterol (TC) and low-density lipoprotein cholesterol (LDL-C) in the blood, and increase the index of high-density lipoprotein cholesterol (HDL-C)/LDL-C and HDL-C/TC. [10,11] Ergosterol (ERG) is a member of the phytosterol family and is derived from edible fungi. It is a biological precursor of vitamin D2 (ergocalciferol) and is the principal component maintaining the integrity of fungal cell membranes.…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the fact that the phytosterols, like those found in soy, compete with cholesterol for intestinal absorption [97]. A 2015 study [98] investigated the effect of 8 weeks of standard soymilk supplementation against the effect of 2 g/day of phytosterols and 10 g/day of inulin-enriched soymilk supplementation. While both groups did see a reduction in LDL-C in both groups, the study group supplementing with the extra phytosterols and inulin saw significantly better results.…”
Section: Soy and Cardiovascular Diseasementioning
confidence: 99%